O inglês como ferramenta para educação ambiental : possibilidades na educação básica - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
The issue of teaching a second language is based on the assumption that it should be a motivating factor for the student to learn, and the pedagogical practice of the English teacher needs to be related to the student's understanding of the true importance of this learning process. In this scenario, the current study aims to investigate teaching and learning activities that involve the environmental issue in the acquisition of new vocabulary in English. Environmental Education, because it is not a subject of the Brazilian Basic Education school curriculum, often being subject to the constitution of the teaching staff and the School's Pedagogical Political Project, it is not exposed or, when it is done, it happens initially, fragmented, isolated in the knowledge of certain disciplines. Environmental Education, the teaching of the English language, likewise needs to be added to global education, seen through an interdisciplinary perspective. Thus, this study aims to show that the union of the foreign language English with the environment theme, in addition to being probable, can be enriching for work in the classroom, insofar as the student makes it possible to use the language as a means of to understand the reality in which it is inserted. The methodology used is based on exploratory research, as it seeks to gather information about a certain object and is qualitative, considering social and cultural elements without being restricted solely to the numerical aspects present in quantitative research. Fieldwork was carried out in which a product was prepared consisting of a Didactic Sequence carried out in person in two stages, the first being in the 3rd bimester of the year 2021 to present the intervention project to teachers and management team and the second stage in the 2nd quarter of 2022 with the application of the Didactic Sequence in five classes. With this perspective, the product aimed to guarantee the skills and competences guaranteed in the National Common Curricular Base (BNCC).
English as a tool for environmental education : possibility in basic education
Keywords: Educação ambiental; Língua inglesa; Interdisciplinaridade; Ensino e aprendizagem; Environmental Education; English language; Interdisciplinarity; Teaching and learning; CIENCIAS HUMANAS::EDUCACAO; LINGUISTICA, LETRAS E ARTES::LETRAS